Is There a Brain Drain in Auditing? The Determinants and Consequences of Auditors Leaving Public Accounting* - Knechel, W. Robert; Mao, Juan; Qi, Baolei; Zhuang, Zili (Contemporary Accounting Research, 2021)
ABSTRACT This study investigates why auditors leave public accounting and the consequences of auditor departures, both of which have been of great concern for audit firms and regulators worldwide. Using data from China and controlling for demographics, we find that audit partners and managers, auditors who generate more revenue, and auditors who provide higher audit quality have a lower likelihood of departure, while non–Big 4 auditors have a higher likelihood of departing public accounting. We also find that an audit firm is likely to lose clients when an auditor departs. Clients who stay with the same firm pay lower audit fees but with no drop‐off in audit quality after a signing auditor departs. In supplementary analyses, we also demonstrate that the determinants and consequences of auditor departures are different for auditors who leave the firm but not the profession (i.e., auditor turnover). Specifically, high audit quality is associated with a lower likelihood of auditor departure, but it increases auditor turnover. We also observe that audit quality is reduced for the clients who stay with an audit firm after highly skilled auditors depart for high‐visibility corporate positions. Our study provides insights that should be of interest to the audit profession, audit firms, and regulators.